Correlation between α-ketoglutarate and the oxidative stress response in patients with coronary heart disease and prognostic analysis of interventional therapy for coronary heart disease - Huantang Deng; Yu Zhang (Frontiers in Cardiovascular Medicine)
ObjectiveTo explore the correlation between α-ketoglutarate and the oxidative stress response in patients with coronary heart disease (CHD) and to analyze the prognosis of CHD patients receiving interventional treatment.MethodsA total of 318 CHD patients admitted from September 2020 to September 2023 were selected and divided into a conservative medical treatment group (159 patients) and an interventional treatment group (159 patients) according to the treatment plan. The interventional treatment group was divided into an event group and a nonevent group according to whether the primary endpoint event occurred; another 59 patients with healthy physical examination results during the same period composed the control group.The resultsThe serum TAC, SOD, CAT, and GSH levels in the conservative medical treatment group were lower than those in the control group (P < 0.05), and the serum MDA level was higher than that in the control group (P < 0.05). α-Ketoglutarate was correlated with oxidative stress indicators (TAC, SOD, CAT, and GSH) in patients with CHD (P < 0.05). A comparison of the α-ketoglutarate levels revealed that the control group > interventional treatment group > medical conservative treatment group (P < 0.05) and that the α-ketoglutarate level in the event group was lower than that in the nonevent group (P < 0.05). The ROC curve analysis results revealed that the area under the ROC curve (AUC) of α-ketoglutarate in the event group after interventional treatment was 702; the AUC of α-ketoglutarate in the no-event group was 802.Conclusionα-Ketoglutarate is related to oxidative stress in patients with CHD. The lower the serum α-ketoglutarate level is, the greater the likelihood that adverse events will occur.